Uji Efektivitas Ekstrak Daun Tin (Ficus Carica L.) terhadap Peningkatan Kadar Glukosa Darah pada Mencit (Mus Musculus) yang diinduksi Aloksan - Nurhikma, Nurhikma; Rahman, Mochammad Erwin; Karim, Abdul Mubdi Ardiansar Arifuddin; Syamsu, Rachmat Faisal; Mokhtar, Shulhana (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to test the effectiveness of fig leaf extract (Ficus Carica L.) on increasing blood glucose levels in mice (Mus Musculus). The type of research is experimental research (true-experimental). The method used in this research is an observational method where direct observations are carried out on laboratory animals to obtain information on the effectiveness of fig leaf extract (Ficus Carica L.) on alloxan-induced increases in blood sugar in mice (Mus Musculus). The results of this study found that fig leaf extract (Ficus carica L.) was effective in reducing blood glucose levels in mice induced by alloxan, showing potential as an alternative therapy for managing diabetes mellitus.